2022
DOI: 10.1155/2022/4817488
|View full text |Cite|
|
Sign up to set email alerts
|

Zonisamide’s Efficacy and Safety on Parkinson’s Disease and Dementia with Lewy Bodies: A Meta-Analysis and Systematic Review

Abstract: Objective. Clinical data has recently shown an association between Parkinson’s disease (PD), Dementia with Lewy bodies (DLB), and zonisamide. The purpose of this study was to thoroughly evaluate the efficacy and safety of zonisamide in PD and DLB. Methods.Pubmed, the Cochrane Library, Web of Science, and Embase databases were searched for all randomized clinical trials (RCTS) on the role of zonisamide in PD and DLB that were completed by April 18, 2022. UPDRS II (off) total score, UPDRS III total score, Daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, zonisamide mitigated the demise of dopamine terminals in the nucleus accumbens as seen in Fig. 5 E. Although zonisamide’s pharmacological profile is complicated as described above, zonisamide was reportedly found to attenuate the loss of dopaminergic neurons in animal studies 31 , 42 , and enhance dopamine synthesis 43 . A positive effect of zonisamide on the dopamine transporter was also reported in the previous 1-year follow-up study with single photon emission computed tomography by using 123 I-FP-CIT 44 .…”
Section: Discussionmentioning
confidence: 85%
“…However, zonisamide mitigated the demise of dopamine terminals in the nucleus accumbens as seen in Fig. 5 E. Although zonisamide’s pharmacological profile is complicated as described above, zonisamide was reportedly found to attenuate the loss of dopaminergic neurons in animal studies 31 , 42 , and enhance dopamine synthesis 43 . A positive effect of zonisamide on the dopamine transporter was also reported in the previous 1-year follow-up study with single photon emission computed tomography by using 123 I-FP-CIT 44 .…”
Section: Discussionmentioning
confidence: 85%
“…The drug has a good long-term tolerability and the majority of adverse events seem to be mild-to-moderate [26,27]. Because of its multidirectional mechanism of action, the efficacy of zonisamide is investigated not only in the treatment of alcohol dependence [2,12,13], but also for other central disorders such as Parkinson's disease and dementia with Lewy bodies [28], migraines [29], and eating disorders [30].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%